Peran Pemangku Kepentingan dalam Tata Kelola Angka Sembilan Coffee - Audina, Septi; Yanti, Rumapea Devi; Agniah, Neng Gita Siti; Amelia, Resti; Aisyah, Nur (Jurnal Digital Bisnis, Modal Manusia, Marketing, Entrepreneurship, Finance, & Strategi Bisnis (DImmensi), 2025)
Effective business governance requires active involvement from all stakeholders. In the context of Angka Sembilan Coffee, the roles of owners, employees, and customers are key factors in supporting operational sustainability. The owner acts as the strategic guide and leader who aligns the business vision with daily implementation. Employees play an important role in providing services, maintaining quality, and contributing to innovation. Customers, in addition to being consumers, also serve as a source of feedback and a channel for promotion through digital interactions. This study adopts a qualitative approach using a case study method to understand the relationships between these three parties through in-depth interviews and observations. The analysis results indicate that collaboration between the owner, employees, and customers creates a governance system that is participatory, adaptive, and responsive to market dynamics. These findings strengthen the application of stakeholder theory in managing MSMEs that prioritize values and the involvement of all related parties.